ON THE QUESTION OF DETERMINING THE EFFICIENCY OF THE MODERNIZATION OF ELECTRIC TRAINS (Transport systems and technologies, 2022)
The article presents the results of the development of a methodological approach to determining the components of the efficiency of the modernization of rolling stock using the example of the exploitation of bushing units with new generation bearings.Factors affecting the amount of additional capital costs for the modernization of electric trains with improved bushing units are analyzed. It is shown that additional capital investments arise due to the costs of research and development works, which are associated with the modernization of electric trains, as well as the costs of purchasing and equipping an electric train with new-generation bushing units instead of basic ones.It is proposed to adapt the calculation of the annual operating costs for the operation of the electric train to the conditions of the specific route served by it and to the existing system of maintaining the rolling stock in a technically sound condition. At the same time, the calculation of operational indicators of the use of the electric train on the route was performed.The influence of electric train modernization on the change in the annual operating costs of the suburban rail transport economy is analyzed. The average annual savings in operating costs for the repair and maintenance of the new generation of bogie assemblies per one electric train of the EPL9t series and the discounted economic effect of modernization for the remaining period of operation of the electric train were determined. It was established that the payback period for additional capital investments does not exceed 5.5 years.The proposed scientific and practical procedure for determining the components of efficiency allows to scientifically justify the feasibility of modernizing electric trains with new-generation bogies, taking into account the remaining period of their operation.
Keywords: rolling stock, electric train, modernization, repair, maintenance, efficiency, operating costs, residual period of operation.